1991
DOI: 10.1159/000129159
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Reaction to Polypropylene Mesh: A Study of Oedema, Blood Flow, and Inflammation in the Abdominal Wall

Abstract: The purpose of the present work was to study the tissue reaction to polypropylene mesh (Marlex®) implanted in three different layers of the abdominal wall, comparable to common clinical practices. The reaction to mesh was compared in terms of tissue oedema, blood flow, and histological appearance in rats. When mesh was placed between muscle layers, blood flow in the abdominal wall was high during the first 4 days after implantation but similar to flow in nonoperated rats 14 and 140 days after implantation. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 9 publications
(11 reference statements)
3
20
1
Order By: Relevance
“…Together with highest values of proliferation (PCNA) at both implantation periods in the PP-mesh group, these findings again underline a more pronounced inflammatory reaction and cell turnover around heavy-weight and small-pored PP-mesh implants. This is consistent with other investigations describing an accented foreign body reaction and fibrosis for heavy-weight polypropylene meshes [14,15,31]. Similar to our previous results [16] and to the observed timedependent decrease of the macrophage index (ED3) in this study, the material-reduced (low-weight) PP + PGcompound mesh was accompanied with a lowered inflammatory activity and decreased rates of cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…Together with highest values of proliferation (PCNA) at both implantation periods in the PP-mesh group, these findings again underline a more pronounced inflammatory reaction and cell turnover around heavy-weight and small-pored PP-mesh implants. This is consistent with other investigations describing an accented foreign body reaction and fibrosis for heavy-weight polypropylene meshes [14,15,31]. Similar to our previous results [16] and to the observed timedependent decrease of the macrophage index (ED3) in this study, the material-reduced (low-weight) PP + PGcompound mesh was accompanied with a lowered inflammatory activity and decreased rates of cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…In the Results section, we have men tioned the formation of considerable granulo mas around the polypropylene monofilaments as well as the increase in the number of foreignbody giant cells. This has also been observed by Dabrowiecki et al [8]. Therefore, we do not agree with the results of Law and Ellis [11] who affirm that the Marlex mesh provokes a weak foreign-body reaction between 8 and 22 weeks after being implanted into the abdominal wall of Sprague-Dawley rats.…”
contrasting
confidence: 96%
“…Dabrowiecki et al [8], in a similar model using the Sprague-Dawley rat, found a greater number of macrophages on day 7 than on day 14 after implantation. This first decrease in the number of macrophages is presumably due to the progression from the acute phase of scar formation to the chronic phase.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The reduction of hernia occurrence on the abdominal wall, after mesh introduction, not only stimulated its use in clinical practice but also stimulated experimental studies in search of a material that would produce less adherence, especially when in visceral contact 14,15,16,17 The classical tissue reaction to prosthesis placement in the peritoneal cavity is characterized by intense inflammatory response which results in the disordered collagen deposition around the prosthesis and in the interstice of the prosthesis's fibers. Fibroblastic reaction provokes mesh encapsulation that is denser in the peritoneal face when compared to the interposed face with the subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%